Using Cutting Video Clip CapCut to Improve the Students’ Speaking Skill at Senior High School - Mardatillah; Nanning; Kalsum (Institut Agama Islam Negeri Palopo, 2024)
This study aimed to improve high school students’ speaking skill by using cutting video clip CapCut in MAN 1 Pare-pare. The study’s findings were beneficial to the teachers, the students and the future researchers. As a result of the teachers’ innovative approach to teaching speaking classes, the students’ discovery of entertaining ways to hone their speaking skill and the future researchers will draw inspiration or references from this study to create better learning materials for their own research. This study used quantitative research applying the pre-experimental method. The population of this research was all the X grade students of MAN 1 Pare-pare. Hence, random sampling was used. The sample was X.1, which consisted of 17 students. This study used the test (pre-test and post-test) in collecting and analyzing the data. Therefore, the study’s findings showed that using cutting video clip CapCut significantly improved the students’ speaking skill. It demonstrated by the students mean score in pre-test (43.29) and in post-test (62.35). It showed that the T-test value was higher that the T-table value (1.86 > 1.753). Thus, it can be concluded that the students’ speaking skill by using cutting video clip CapCut significant better after the treatment. Keywords: Cutting Video Clip, CapCut Application, Speaking Skill.